Knee Lyme Arthritis in Pediatric and Adolescent Patients May Be Associated With Meniscal Changes on MRI - Matthew D. Milewski, MD; Kirsten Ecklund, MD; Sang Won Lee, MSc; Ryan P. Coene, MS; Ryan M. Sanborn, BA; Emma C. Gossman, BS; Patricia E. Miller, MS; Benton E. Heyworth, MD; Yi-Meng Yen, MD, PhD (JBJS Open Access)
Background:. Lyme arthritis is a common manifestation of late-stage Lyme disease in pediatric and adolescent patients. Patients with Lyme arthritis typically present with atraumatic knee effusion and may undergo magnetic resonance imaging (MRI) to aid in diagnosis. The incidence of meniscal pathology on MRI in association with Lyme arthritis is unknown. This study aims to evaluate the incidence of meniscal pathology on MRI in young patients with Lyme arthritis. Methods:. Patients (<18 years old) presenting with a unilateral knee effusion from 2009 to 2019 with a positive Lyme antibody serologic test, MRI within 2 weeks of the positive test, and ultimate diagnosis of Lyme arthritis were included in the study. MRI, which was performed to distinguish Lyme arthritis from other causes of knee effusion, underwent analysis by a pediatric musculoskeletal radiologist. Meniscal signal abnormality was graded as follows: grade 1 = globular, grade 2 = linear nonsurfacing, and grade 3 = surfacing tear. Results:. Eighty-seven patients (10.6 ± 3.9 years, 71.3% male, 67.8% White) were included. Fourteen (16%) patients had meniscal changes (grade 1: n = 4 [5%]; grade 2: n = 3 [3%]; grade 3: n = 7 [8%]). Thirteen of the 14 patients (93%) with meniscal changes on MRI were treated only with oral antibiotics, with resolution of knee symptoms and return to sports, whereas 1 patient (7%) underwent arthroscopic partial meniscectomy. Conclusions:. Of the 87 pediatric patients with serologically confirmed Lyme arthritis and MRI of their affected knee, 16% had a coexistent meniscal abnormality on MRI, but only 1 patient overall required surgical treatment related to the meniscus. Physicians should be aware of potential MRI meniscal changes in pediatric and adolescent patients who present with symptomatic knee effusion because of Lyme arthritis. Future research to evaluate the physiologic effects of Lyme arthritis on meniscal tissue is needed. Level of Evidence:. Level IV Case Series. See Instructions for Authors for a complete description of levels of evidence.